2004
DOI: 10.1300/j070v13n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Trauma, Spirituality, and Psychopathology

Abstract: This study assessed the association between spirituality and psychopathology in a group of sexual abuse victims and controls with a focus on whether spirituality moderated the association between sexual trauma and psychopathology. Seventy-one sexual trauma victims were compared to 25 control subjects on spiritual well-being, the Eating Disorder Examination, the PTSD Symptom Scale, and the SCID-I/P. The data showed that the two groups did not differ in terms of spiritual well-being. Sexual trauma status was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Ujemne zależności między duchowością a nasileniem objawów zespołu stresu pourazowego uzyskano m.in. w badaniach Afroamerykanek, które doświadczyły przemocy domowej [27] czy ofiar przestępstw seksual nych [28].…”
Section: Omówienie Wynikówunclassified
“…Ujemne zależności między duchowością a nasileniem objawów zespołu stresu pourazowego uzyskano m.in. w badaniach Afroamerykanek, które doświadczyły przemocy domowej [27] czy ofiar przestępstw seksual nych [28].…”
Section: Omówienie Wynikówunclassified
“…However, greater levels of spirituality have been associated with fewer anxiety symptoms among patients with advanced illness [11] and with lower posttraumatic symptom severity among survivors of violent trauma [12]. Krejci et al [13] found that although sexual abuse victims and controls did not differ in terms of spiritual well-being, lower psychopathology including PTSD symptom scores, were associated with increased spiritual well-being in both groups.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they are also reported to be able to adopt cognitive appraisal and positive reframing strategies (Oaksford and Frude, 2003) as well as spiritual/religious coping (Krejci et al, 2004;Lawson et al, 1998;Perkins and Jones, 2004).…”
mentioning
confidence: 99%